PREVALENCIA DE Trypanosoma vivax EN BOVINOS DE LA PROVINCIA DE CORONEL PORTILLO, UCAYALI - Quispe A., Patricia (2003)
The objective of the study was to determine the prevalence of Trypanosoma sp. in healthy cattle that are reared in four districts (Callería, Campo Verde, Masisea and Yarina) of the Coronel Portillo Province, Ucayali, using the Woo and the buffy coat stained with Giemsa techniques. The latter was also used to determine the species of trypanosome involved. A total of 289 blood samples were collected in May-July, 2000 from crossbred Zebu cattle. Animals were 8 months till 16 years of age, and managed under an extensive rearing system. The morphometric identification showed that the prevalent species was Trypanosoma vivax. The prevalence of T. vivax was 22.2 ± 4.8% when the Woo technique was used and 5.9 ± 2.7 when the stained smear was used. The Campo Verde district had the higher frequency of positive animals (97%, 62/64). None of the animals showed clinical signs of the disease and only 8 animals had a low hematocrit value. No significant relationship between the presence of the parasite and the low hematocrit was found (p>0.05). It was concluded that the observed prevalence was relatively high, whereas animals have a subclinic or benign infection.